Development and assessment of validity and reliability of a checklist to evaluate the Circulating and Scrub Skills of Operating Room Novices (CSSORN checklist) - Morteza Nasiri; Shahrzad Yektatalab; Marzieh Momennasab; Fatemeh Vizeshfar (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Assessment of circulating and scrub skills is an important issue in operating room (OR) programs. However, there is a lack of well-designed tools that are specifically developed for this purpose. Hence, this study aimed to develop and determine the validity and reliability of a checklist to measure the circulating and scrub skills of OR novices. MATERIALS AND METHODS: This cross-sectional methodological study was conducted among 124 OR technology students who were selected during three consecutive academic years (2019-2020 to 2021-2022). The developed checklist was evaluated with face validity, content validity (quantitative and qualitative), construct validity (known-groups validity), criterion-related validity (concurrent and predictive validities), internal consistency (Kuder-Richardson 20, KR-20), and inter-rater reliability (intra-class correlation coefficient, ICC). Known-groups validity was evaluated by comparing the difference between the checklist scores of first-semester and third-semester students using independent samples t-test. Additionally, concurrent and predictive validities were evaluated by ICC through measuring the correlation between the total score of checklist and grades of a multiple-choice test and two clinical apprenticeship courses, respectively. Data were analyzed in the Statistical Package for Social Sciences software. RESULTS: After reconciling the preliminary checklist in terms of face and content validities, a checklist with 17 sub-scales and 340 items called "Circulating and Scrub Skills of Operating Room Novices (CSSORN)" was developed. Regarding the known-groups validity, the third-semester students had higher scores compared to the first-semester students (p < 0.001 in most sub-scales). Besides, the total score of checklist showed a significant correlation with the criteria of concurrent and predictive validities (ICC = 0.64, ICC = 0.72; P < 0.001). The KR-20 for the entire checklist was 0.90 (range: 0.60-0.93). The ICC for inter-rater reliability was also 0.96 for the entire checklist (range: 0.76-0.99, P < 0.001 in all sub-scales). CONCLUSION: The CSSORN had appropriate validity and reliability to be used for measuring the circulating and scrub skills of OR novices. To shed light on the findings, further testing of this checklist on larger populations and in different contexts is suggested.